2004
DOI: 10.1080/10428190410001714016
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ZAP-70 Protein Correlates with Disease Stage in Chronic Lymphocytic Leukemia and is Associated with, but not Generally Restricted to, Non-mutated Ig VHStatus

Abstract: The mutational status of immunoglobulin variable region genes (Ig VH) is a well established prognostic parameter in chronic lymphocytic leukemia (CLL). Recently, a subset of genes with a characteristic expression profile correlating with the mutational status of B-CLLs has been identified. One of the overexpressed genes in the prognostically unfavorable group of CLL patients with unmutated Ig VH genes encodes for the protein tyrosine kinase ZAP-70, which is physiologically involved in T-cell signaling. Since Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 16 publications
2
19
1
2
Order By: Relevance
“…High ZAP-70 expression was also shown to be an independent poor prognostic factor in CLL, illustrating that it is more than just a surrogate marker for the mutational status in CLL (13). Moreover, Kim et al demonstrated that high expression of ZAP-70 protein correlates with Binet disease stage B or C in CLL and is associated with, but not generally restricted to, non-mutated IgVH status (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High ZAP-70 expression was also shown to be an independent poor prognostic factor in CLL, illustrating that it is more than just a surrogate marker for the mutational status in CLL (13). Moreover, Kim et al demonstrated that high expression of ZAP-70 protein correlates with Binet disease stage B or C in CLL and is associated with, but not generally restricted to, non-mutated IgVH status (10).…”
Section: Discussionmentioning
confidence: 99%
“…Samples considered high by the quantitative method are marked in gray. (4,10,11,13,14,26). On the basis of this data, ZAP-70 has become an important prognostic factor in CLL, and may be utilized for risk stratification and possible risk adapted therapy in CLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Nevertheless, ZAP70 expression does not always correlate with the mutational status of Ig genes; in fact it does not correlate with more than 90% of cases. 29 Very recently, Rassenti and colleagues 30 better defined the correlation between Ig mutational status and ZAP70 expression levels. They showed that ZAP70 was highly expressed in only 71% of UM-CLL cases and in 17% of M-CLL cases with an overall concordance of 77%.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, CD38 expression does not always correlate with the IgV H mutational status [23][24][25] rather it appears to be an independent prognostic marker in B-CLL. 26 In addition, expression of ZAP70 kinase was first recognized to correlate with Ig mutational status and prognosis, 27,28 but recent studies have shown a discordance between ZAP70 and Ig mutational status, 29 although ZAP70 maintains an important prognostic independent value. 30 Here we describe a rapid and simple method to analyze the nucleotide sequence of the variable portion of Ig heavy chain gene using amplicons obtained with degenerate primers commonly used for diagnostic B-cell clonal detection purposes.…”
mentioning
confidence: 99%